A Contrastive Study on Image Repair Strategies in Chinese and American Corporate Apologies - Li, Chenyang; Xu, Zhanghong (International Journal of Linguistics, 2023)
Nowadays, frequently-happening wrongdoings have seriously damaged the corporate image and threatened the survival of corporations. For companies in crises, an appropriate apology has become a vital strategy to repair corporate image. Remarkable achievements have been made in the contrastive study of corporate apologies, but there is still much to be explored about Chinese and American corporate apologies. Therefore, this paper investigates the differences of the image repair strategies employed in Chinese and American corporate apologies, in order to help corporations handle crises in a cross-cultural context. With AntConc 2019, the paper first analyzes the major linguistic devices in 100 Chinese and American corporate apologies, and then finds out the differences of image repair strategies and the underlying factors through qualitative analysis, based on Benoit’s image repair strategies and Adaptation Theory. The results show that (1) Chinese companies show their solemnity and sincerity in the crisis through person deixis such as company and customer and strengtheners such as again, seriously and first time, while American companies use more demonstrative pronouns like this, these and it, and politeness words like please, hope and thank to mitigate crisis conflicts. Meanwhile, when providing compensation and follow-up services, American ones would use if-conditionals to control the cost of the apology. (2) Reducing offensiveness and Mortification are the two most commonly used strategies, respectively accounting for 37.7% and 36.3%. In mortification, asking for forgiveness is often used in American corporate apologies (11.3%), while accepting the blame is more common in Chinese corporate apologies (11.1%). When reducing offensiveness, Chinese corporations would choose bolstering (20.9%) and transcendence (10.5%), while American ones prefer compensation (17.6%) and valuing the customer (13.9%). (3) Chinese culture emphasizes collectivism and high-power distance, while American culture emphasizes individualism and low-power distance, which accounts for the difference of image repair strategies in Chinese and American corporate apologies. This paper can act as a complement to the contrastive research on American and Chinese corporate apologies and provide references for corporate communication in a cross-cultural context.